Religiosity, Institutional Policy, and Climate Awareness in Shaping Environmental Behaviour Among Gen Z Students at Islamic and Catholic Universities - M Pasqa; Asep Muhamad Iqbal (Indonesian Journal of Religion and Society, 2026)
This study examines how religiosity, institutional environmental policies, and climate change awareness shape pro-environmental behaviour among Generation Z students at an Islamic and a Catholic university in Indonesia. Using a convergent mixed-methods design, it integrates survey data from 300 students with six in-depth interviews to assess how faith-based institutions expect ecological values to inform daily practices. PLS-SEM results indicate that climate change awareness plays the most central role in encouraging pro-environmental behaviour, while institutional environmental policy primarily strengthens awareness rather than directly influencing habits. Religiosity functions more as a broad moral reference than as a consistent guide for concrete environmental actions. The research findings show that students’ climate awareness develops largely through everyday experiences and digital exposure, rather than through formal religious instruction or campus initiatives policy. The study challenges faith-based universities to reconceptualise environmental education from abstract theological instruction toward experiential programs actively involving students in sustained environmental practices, integrating religious values into lived habits through channels that genuinely shape Gen Z consciousness.